EXPERIENCE OF UZBEKISTAN AND FOREIGN COUNTRIES IN ESTIMATION OF CADASTRAL VALUE AND TECHNICAL VALUE OF BUILDINGS AND STRUCTURES - Mirzaakbarov Ozodbek Askarjonovich; Uspankulov B. M. (Bright Mind Publishing, 2025)
This article examines the methods of determination and technical evaluation of cadastral value of buildings and structures. The economic and legal basis of cadastral valuation, the impact of technical indicators on cadastral value, as well as the methods used in technical estimation are studied using a comparative approach. The national experience is analyzed on the basis of relevant legislation and regulations of the Republic of Uzbekistan (for example, Law on Land Cadastre, Resolution of the Cabinet of Ministers No. 146) and comparison with advanced evaluation systems in the practice of European countries such as Germany, France and the Netherlands. The article discusses the role of technical assessment results in the formation of cadastral value, the powers of appraisers, the level of digitalization and the introduction of modern technologies. In total, practical proposals were given on introducing effective foreign experiences for Uzbekistan.
Keywords: Cadastral value, technical assessment, land cadastre, real estate, appraiser, European experience, Uzbekistan, digitalization, valuation methodology